1994
DOI: 10.1254/jjp.65.35
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Menatetrenone on the Decrease in Calcium Balance Induced by Vitamin K-Deficient Diet and Sodium Loading in Rats.

Abstract: ABSTRACT-The effects of menatetrenone (2-methyl-3-tetraprenyl-1,4-naphthoquinone, MK-4) on cal cium balance were studied in male Sprague-Dawley rats. Experiment 1: Rats in metabolic cages that were fed a vitamin K-deficient diet and injected daily with latamoxef (100 mg/kg, i.p.) were either treated or untreated with MK-4 for 7 days. Daily food intake, urine volume and feces weight were determined, and calcium concentration in these samples was measured. Calcium balance was calculated as the difference between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
1
8
1
Order By: Relevance
“…These findings were consistent with the report of Arjmandi et al (26), and O'Loughlin and Morris (27). We have already reported that vitamin K 2 improved a decrease in intestinal Ca transport which was induced by sodium loading in rats (17). In this study, however, the intestinal Ca transport was higher in the vitamin K2 administration groups than in the OVX-control group, but not to a significant extent.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings were consistent with the report of Arjmandi et al (26), and O'Loughlin and Morris (27). We have already reported that vitamin K 2 improved a decrease in intestinal Ca transport which was induced by sodium loading in rats (17). In this study, however, the intestinal Ca transport was higher in the vitamin K2 administration groups than in the OVX-control group, but not to a significant extent.…”
Section: Discussionsupporting
confidence: 93%
“…The S/M ratio in the shamtreatment group was 3.37. In this study, in contrast, the S/ M ratio in the sham-treatment group was lower (1.18) than that in our previous study (17). This result is considered due to the use of very aged (29-week-old) Fischer rats.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Kobayashi et al (3) showed that vitamin K supplementation in severe calcium/ magnesium-deficient rats improved the abnormal decreases in serum calcium and magnesium levels and abnormal increases in serum PTH level and renal cal cium concentration. Tomiuga et al (6) showed that vitamin K supplementation in vitamin K-deficient and sodium-loading rats prevented the reduction in intesti nal calcium absorption. Thus, vitamin K supplementa tion may have the potential to increase renal and intes tinal retention.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, several reports indicate an important role for Vitamin K in bone health. Administration of Vitamin K results in an increase in bone-mineral density and a reduction in bone resorption in humans [3][4][5][6] and rodents [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%